NATURAL RADIOACTIVITY LEVELS AND RADIOLOGICAL HAZARDS INDICES OF SOIL SAMPLES FROM SELECTED MINING SITES, DANGE-SHUNI, SOKOTO STATE, NIGERIA - Ahijjo, Yusuf Musa; Baba-Kutigi, A. N. (FUDMA Journal of Sciences, 2023)
Elevation of environmental radioactivity is a growing concern that requires monitoring and measurement via nuclear analytical procedures and have been conducted from Dange-Shuni in this study. The unabated mining activities whose motive is to constantly keep industries running on locally sourced minerals and raw materials often leave the host communities with heavy burden of radioactivity impacts that have be monitored in this study. this should explicitly and clearly state main objectives of the work. Hyper Pure Germanium detector coupled to a Multi-Channel Analyzer (MCA) was used for gamma-ray spectrometry to ascertain the activity concentration results of ,,in 15 packs of homogenized soil samples collected from mining sites, Dange-Shuni LGA, Sokoto State, Nigeria. Mutually exclusive and collectively exhaustiveness approach of sampling was adopted in order to overcome the limitations of large and diverse nature of mining localities terrain. Results obtained from gamma-ray spectroscopy reveals a range of 30.72.9 to 95.67.2, 30.72.9 to 95.67.2 and 499.2051.5 to 971.2421.5 for ,and respectively. The mean values were calculated to be 58.04, 54.5 and 767.62 respectively. The radiological hazards of , , , , ,  and  were obtained for the results of activity concentration ascertained in this study. The results were found in elevations to the world mean values in comparison which is an implication of dangers of environmental radioactivity to the generality of the dwellings. These results are in good agreements with previous studies and hence, suggests for similar investigation to be conducted.
Keywords: HPGe – Detector; Gamma-rays Spectroscopy; Mining-sites; Dange-Shuni; Environmental Radioactivity